COPD: Does Inpatient Education Impact Hospital Costs and Length of Stay?. Issue 4 (2nd October 2019) - Hosseini, Hengameh M.; Pai, Dinesh R.; Ofak, Daniel R.
Abstract: Background: Chronic Obstructive Pulmonary Disease (COPD) is the third leading cause of death in the United States and costs approximately $50 billion in annual healthcare costs. Certain interventions such as COPD inpatient education programs have demonstrated effectiveness in reducing healthcare utilization and reducing healthcare associated costs. Purpose: To assess the effectiveness of chronic obstructive pulmonary disease (COPD) inpatient education using existing respiratory therapy staff in an academic health system. Methodology/Approach: This retrospective observational study employed a matched case-control design. Inpatients admitted with a COPD related condition in this study received self-management interventions from Registered Respiratory Therapists (RTs). The sample includes retrospective administrative and medical record data on 84 inpatients with a diagnosis of COPD admitted in 2016 through 2017. Patients received self-management interventions at the bedside by trained RTs while admitted to acute care areas, progressive care units and intermediate care units. Effectiveness of inpatient education was compared before and after the interventions. Hospitalization costs and length of stay (LOS) are the primary outcome measures. Results: Statistical analyses revealed that inpatient COPD education appears to reduce hospital length of stay and associated costs. Post hoc regression analyses revealed that age, gender, marital status, and number of visits were significantly associated with LOS; whereas, smoking, LOS, and number of visits were significantly associated with hospitalization costs. Practice Implications: COPD patient education may be an effective strategy at reducing hospital costs and healthcare utilization overall. Empowering patients to take responsibility for their own health outcomes by improving self-efficacy has proven to demonstrate value.